Identification of Formalin in Food Sold in Ciamis by Thin Layer Chromatography - Indra Permana; Imas Irmasyanti (LPPM STIKes Muhammadiyah Ciamis, 2023)
Formalin is a non-food preservative that is now widely used to preserve food. Formaldehyde is the trade name of formalin consisting of a mixture of formaldehyde, methanol and water. Formaldehyde on the market has various formaldehyde levels, between 20% - 40%. Formalin is a preservative that is prohibited for use in food products. However, there are traders who use formaldehyde in food products. The purpose of this study was to identify formaldehyde in food sold in Ciamis District. This study is a description of the phenomena found in the field, namely the presence of foods containing formalin. The method used was KmnO4 reagent and Thin Layer Chromatography. The results showed that of the 5 food samples tested using KmnO4, positive results were obtained for tofu, salted fish, fresh fish, and chicken meat which were marked by a loss of purple color during testing. With the Thin Layer Chromatography method, the Rf value of tofu was 0.60, salted fish was 0.61, fresh fish was 0.61 and chicken meat was 0.62